Teacher training, educational attention to pupil with multidisability and Sensory-motor Stimulation - María José Martínez Segura (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This conference describes the concept of human and sustainable development, distinguishing of the merely economic thing. The University must be on the one hand an educator ( not only instructing) and on the other hand human (not only professional). The education for which one pleads implies the acquisition of Ethical values contributing the University activity to the human and sustainable development. What has been done in this line up to now? Some important experiences are announced, carried out for different entities compromised with the justice. What way must the University follow? The bases of a curricular system are showed with pupils and teachers like important elements; in the cognitive place, taking charge of the reality. From the attitudinal point of view, to face with the reality and from the procedural point of view, to take charge of the reality.